Field trial assessing the antimicrobial decontamination efficacy of gaseous ozone in a public bus setting - Neves, Erica Sena (2023)
The widespread COVID-19 pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) necessitated measures aimed at preventing the spread of SARS-CoV-2. To mitigate the risk of fomite-mediated transmission, environmental cleaning and disinfection regimes have been widely implemented. However, conventional cleaning approaches such as surface wipe downs can be laborious and more efficient and effective disinfecting technologies are needed. Gaseous ozone disinfection is one technology which has been shown to be effective in laboratory studies. Here, we evaluated its efficacy and feasibility in a public bus setting, using murine hepatitis virus (a related betacoronavirus surrogate) and the bacteria Staphylococcus aureus as test organisms. An optimal gaseous ozone regime resulted in a 3.65-log reduction of murine hepatitis virus and a 4.73-log reduction of S. aureus, and decontamination efficacy correlated with exposure duration and relative humidity in the application space. These findings demonstrated gaseous ozone disinfection in field settings which can be suitably translated to public and private fleets that share analogous characteristics.